The influence various sources of fluctuation on the statistical parameters of the vertical cavity surface emitting lasers output radiation - Burov, Leonid I.; Gorbatsevich, Alexander S.; Labatsevich , Pavel M. (Journal of the Belarusian State University. Physics, 2019)
Based on statistical modeling, a numerical analysis of the effects exerted by different factors (fluctuations of the spontaneous emission intensity, nonequilibrium carrier concentration, injection current density) on the statistical characteristics of radiation at the output of surface emitting semiconductor lasers in the region of polarization instability has  been performed. In this region the effect of fluctuations is maximal, offering the possibility for substantiated conclusions  about relative effects of the parameters. In a theory of semiconductor lasers it is thought that the intensity fluctuations  of spontaneous emission represent the dominant source of fluctuations, whereas all other sources may be neglected.  As demonstra ted by the results of conducted statistical modeling, this statement is too rigorous; moreover, such a source is  not dominant. Taking into consideration fluctuations of the carrier concentration, which result in fluctuations of the amplification factor, we can derive a complete set of the relationships observed experimentally. This result cannot be associated  with features our model because in our theory spontaneous emission is a significant factor. If the influence of spontaneous  emission would be the dominant factor, it would affect the simulation results. The obtained data make it possible to doubt  the key role of the spontaneous emission intensity fluctuations in the process of statistical characteristics formation for the  output radiation and to take into account fluctuations of the nonequilibrium carrier concentration.
Keywords: semiconductor laser; polarization; fluctuations